Cryogenic Equipment in Minimally Invasive Surgery - Chizh, Nikolai A. (Problems of Cryobiology and Cryomedicine, 2018)
In this review we analyzed the technological methods and apparatuses, applied in minimally invasive cryosurgeries. Here, we presented the methods of cooling, the main structural components of modern cryosurgical units and coolants, used in these systems. The article covers the issues, related to the requirements for cryogenic equipment in the process of its designing. Brief technical characteristics of the most known cryosurgical units and the information on the post-application therapeutic efficiency were presented. Â  Probl Cryobiol Cryomed 2018; 28(3): 200â€“211